Evaluating the Role of Homoeopathy in Modulating Hereditary Predisposition to Chronic Diseases (Homoeopathy for All, 2025)
Chronic diseases continue to exert  a heavy burden on global health,  with a significant proportion rooted  in hereditary predispositions. This  article explores the potential of ho moeopathy as a therapeutic modality  for addressing inherited tendencies  to chronic ailments. Drawing upon  classical homoeopathic literature,  clinical methodologies, and personal  motivations, this study aims to eval uate the efficacy of individualized  homoeopathic treatment in modu lating hereditary predispositions to  chronic diseases.
Keywords: Homeopathy; Hereditary Predispositions; Chronic Diseases; Personalized Medicine; Disease Pre vention; Individualized Treatment